Identification and pathway analysis of metabolic biomarkers of gastric acid aspiration-induced lung injury in mice - Chun-qin Chu; Nan-nan Zhang; Peng Ding; Wei Feng; Xiao Zhang; Li-peng Zhao; Cai-feng Shi; Yong-hua Li; Jun-tao Wang (European Journal of Medical Research)
Abstract Acute lung injury (ALI) induced by aspiration of gastric acid is a complex and serious disease with high morbidity and mortality, and the lack of sensitive biomarkers hampers the timely treatment. This study aimed to reveal the metabolic changes in the serum and lung tissues in a mouse ALI model. We established the model by endotracheal hydrochloric acid infusion and verified the model by histopathological staining, bronchoalveolar lavage fluid protein level, and cell counts. Serum and lung tissues were assessed by a liquid chromatograph–mass spectrometer to identify the differential metabolites, followed by enrichment analysis and pathway analysis using an online metabonomic database. Metabolomic analysis results showed significant differences between the model group and the control group. A total of 40 differential metabolites in the serum and 30 in lung tissues were identified. Pathway analysis showed that the changes were mainly located in fatty acid metabolism, lipid metabolism, carnitine metabolism, and amino acid metabolism. The network analysis revealed a perturbation of nitric oxide signaling, nNOS signaling, glucocorticoid receptor signaling, FXR/RXR activation, and mTOR signaling. These findings may provide some novel biomarkers and new insights for further understanding and studying the pathogenesis of gastric acid aspiration-induced ALI.